Safe-Sex Behavioral Intention of Chinese College Students: Examining the Effect of Sexual Knowledge Using the Theory of Planned Behavior - Wang, Xin; Jin, Yuanqing; Tian, Mengqin; Zhuo, Qinzi; Lin, Chien-Liang; Hu, Pengfei; Wang, Ting (Frontiers in Psychology, 2022)
The issue of safe sexual behavior among college students has been the focus of many contemporary studies. Especially in China, Chinese families have been reluctant to disclose the issue of sexual behavior, so understanding and trying to explore the extent of college students’ knowledge about sexual behavior and the promotion of safe sexual behavior is an important and urgent issue to be discussed. Therefore, based on the Theory of Planned Behavior (TPB), a cognitive-behavioural approach, this study conducted an in-depth investigation on the factors influencing Chinese college students’ sexual behavioral intentions, especially since TPB has been widely used to predict human social behavior. This study combines the relevant literature to propose a comparison of differences in sexual knowledge as a model for the TPB. Based on the results of statistical analysis, this study found that subjective norms and behavior control are important variables that influence college students’ safe sexual behavior. Second, attitudes and safe sexual behavioral intentions were found to be influential in groups with high sexual knowledge understanding. In addition, behavior control and subjective norms affected the difference in comparative sexual knowledge. Finally, this study proposes relevant research recommendations and directions based on the results to suggest practical directions for the development of sexual education in China.